Sistem Informasi Jadwal Perkuliahan Menggunakan Media Televisi (Studi Kasus Pada Jurusan Teknik Informatika Upn “Veteran” Yogyakarta) - Andani, Sundari Retno; Wibowo, Subastian; Poningsih, Poningsih (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2017)
Students are always confused with a schedule of lectures, about time of lectures, room that will be used, even about come or not the lecturer on class. As a result, students must always go to the education department to inquire this issue. It is very ineffective. But there is no system that helps students in overcoming this problem. In this paper, the authors build a system with the title is the information system of the schedules of lectures using television. The system is built using Delphi 6.0 programming language and uses Microsoft Access 2003 as the database. To operate this system requires a CPU and a television screen as an output device. This system provides information on the schedule of lectures to the students through a television screen. Information provided includes schedule of lectures, room that will be used, the certainty of the lecture will take place, and informing announcements and activities that will take place. These systems also support the effectiveness of the performance of educational staff in the conduct of daily operations.